Hypothalamic control of brown adipose tissue thermogenesis - Labbé, Sebastien M.; Caron, Alexandre; Lanfray, Damien; Monge-Rofarello, Boris; Bartness, Timothy J.; Richard, Denis (Frontiers in Systems Neuroscience, 2015)
It has long been known, in large part from animal studies, that the control of brown adipose tissue (BAT) thermogenesis is insured by the central nervous system, which integrates several stimuli in order to control BAT activation through the sympathetic nervous system (SNS). SNS-mediated BAT activity is governed by diverse neurons found in brain structures involved in homeostatic regulations and whose activity is modulated by various factors including oscillations of energy fluxes. The characterization of these neurons has always represented a challenging issue. The available literature suggests that the neuronal circuits controlling BAT thermogenesis are largely part of an autonomic circuitry involving the hypothalamus, brainstem and the SNS efferent neurons. In the present review, we recapitulate the latest progresses in regards to the hypothalamic regulation of BAT metabolism. We briefly addressed the role of the thermoregulatory pathway and its interactions with the energy balance systems in the control of thermogenesis. We also reviewed the involvement of the brain melanocortin and endocannabinoid systems as well as the emerging role of steroidogenic factor 1 neurons in BAT thermogenesis. Finally, we examined the link existing between these systems and the homeostatic factors that modulate their activities.